Penguatan Pendidikan Karakter Berbasis Kearifan Lokal melalui Media Video: Studi Kasus di Desa Terutung Seperai, Aceh Tenggara - Nursafiah, Nursafiah; Sukma, Mairi; Akram, Habibul; Purnama, Anton; Maufira, Rila; Hasan, Muridha; Hartono, Makmur; Agustyan D, Rahmad; Dari, Ulan; Arivatussaqdiyah, Arivatussaqdiyah; Ladipin, Ladipin; Bahrul Ilmi; Reviza , Liza; Nurlaila, Nurlaila; Sari, Bungsu Keumala; Fajriana, Nurul (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Strengthening character education through local wisdom is essential for shaping morally upright generations while preserving cultural heritage amid globalization. This community service program integrated the cultural values of Terutung Seperai Village, Southeast Aceh—such as the tradition of cooking lemang and fostering mutual understanding—into character learning using contextual and adaptive video media. Twenty participants from Ar-Raudhah TPQ (Islamic junior-level school) were engaged through lectures, discussions, and interviews in a participatory format. Videos adapted from online sources were modified in narrative, visuals, and moral content to reflect local culture. Implementation included preparation, media selection, outreach, execution, evaluation, and follow-up. The results showed improved understanding of cooperation, tolerance, discipline, responsibility, and religiosity, with high participant engagement and commitment to applying these values in daily life. Video media proved effective for delivering moral messages, preserving cultural identity, and engaging digital-native learners. This initiative offers a replicable, interactive, and sustainable character education model rooted in local wisdom.